Will Spain is different? balance of the Maghreb immigration in Spain - López García, Bernabé; Ramírez, Angeles (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Dating from 1991, year in which the first large process of regularization of immigrants takes place in Spain, one can say that immigration in our country has been consolidate. Of all immigrants, moroccans are the most significant group speaking in terms of numbers. The article pretends to reconstruct the process of immigration in Spain by looking at the history of moroccan immigration. A look into immigration through the issues of legality/illegality, measures for the control of flows and international relationships, as well as immigration through the analysis of the processes of settlement and the presence of women, are the two great axes on which the article builds.